A method for generating an illusion of backwards time travel using immersive virtual reality—an exploratory study - Friedman, Doron; Pizarro, Rodrigo; Or-Berkers, Keren; Neyret, Solène; Pan, Xueni; Slater, Mel (Frontiers in Psychology, 2014)
We introduce a new method, based on immersive virtual reality, to give people the illusion of having travelled backwards through time to relive a sequence of events in which they can intervene and change history. The participant had played an important part in events with a tragic outcome - deaths of strangers – by having to choose between saving 5 people or 1. We consider whether the ability to go back through time, and intervene, to possibly avoid all deaths, has an impact on how the participant views such moral dilemmas, and also whether this experience leads to a re-evaluation of past unfortunate events in their own lives. We carried out an exploratory study where in the ‘Time Travel’ condition 16 participants relived these events three times, seeing incarnations of their past selves carrying out the actions that they had previously carried out. In a ‘Repetition’ condition another 16 participants replayed the same situation three times, without any notion of time travel. Our results suggest that those in the Time Travel condition did achieve an illusion of ‘time travel’ provided that they also experienced an illusion of presence in the virtual environment, body ownership and agency over the virtual body that substituted their own. Time travel produced an increase in guilt feelings about the events that had occurred, and an increase in support of utilitarian behavior as the solution to the moral dilemma. Time travel also produced an increase in implicit morality as judged by an implicit association test. The time travel illusion was associated with a reduction of regret associated with bad decisions in their own lives. The results show that when participants have a third action that they can take to solve the moral dilemma (that does not immediately involve choosing between the 1 and the 5) then they tend to take this option, even though it is useless in solving the dilemma, and actually results in the deaths of a greater number.